Pengaruh Current Ratio, Debt To Equity Ratio Dan Debt To Asset Ratio Terhadap Return On Assets Pada Perusahaan Transportasi Dan Logistik Yang Terdaftar Di Bursa Efek Indonesia Tahun 2016-2020 - Delima Delima; Eka Purnama Sari (Student Research Journal, 2023)
This study aims: To determine the effect of the Current Ratio , Debt to Equity Ratio and Debt to Asset Ratio to Return On Assets in Transportation and Logistics Companies listed on the Indonesia Stock Exchange 2016-2020. The method in this study uses a quantitative approach, the number of samples in this study were 40 companies. The data collection technique in this study uses data obtained from financial reports at Transportation and Logistics companies listed on the Indonesia Stock Exchange 2016-2020. The data analysis technique used multiple linear regression and descriptive statistics. Based on the research, it shows that the Current Ratio has no negative and insignificant effect on Return On Assets with the Asymp value. Sig. (2-tailed) of 0.508, the Debt to Equity Ratio has no negative and insignificant effect on Return On Assets with an Asymp value. Sig. (2-tailed) of 0.096, the Debt to Asset Ratio has a positive and significant effect on Return On Assets with the Asymp value. Sig. (2-tailed) of 0.014, and simultaneously Current Ratio, Debt to Equity Ratio and Debt to Asset Ratio jointly have a positive and significant effect on Return On Assets with an Asymp value. Sig. (2-tailed) of 0.043